Effect of Soft Cheese in Reducing of Lipid Profile and Liver Enzymes for Rats with Fat Disorder - Hiba Sabah Elttayef1, Mohammed Ahmed Jassim2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: This study was designed to determine the impact of soft cheese upon total cholesterol (TC),triglycerides (TG), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL),very low-density lipoprotein cholesterol (VLDL) and the efficacy of liver enzymes AST, ALT, and ALP inhyperlipidemia experimental Sprague-Dawley rats. Materials & Methodology: Rats were divided into fivegroups (six rats each), healthy control group, hyperlipidemia control group, and three hyperlipidemia groupswere fed on regular soft cheese (T1), cheese supplementation with probiotics (T2), and cheese supportedwith Nigella sativa L (T3). Following 28 days, Result: the results revealed a significant decrease (p<0.05) intotal cholesterol in groups of rats that were feeding on chees T1, T2 and T3 (179.83, 138.71 and 135.06 mg/dl, respectively) compared to hyperlipidemia control group (250.98 mg/dl), T1, T2 and T3 groups showed asignificant decrease in LDL levels (153.45, 104.39, 97.47 mg/dl respectively) compared to hyperlipidemiacontrol groups (246 mg/dl). However, an increase of HDL levels were noticed in the same groups in contrast,T3 group revealed significantly decreased in the liver enzymes(28.45, 67.29, 98.16 IU/L) of ALT, AST andALP respectively compared to hyperlipidemia control group (41.27, 88.35, 108.72)IU/L respectively.